Analysis Of Factors Associated With Quality Of Work Life Among Tofu Factory Workers In Jambi City - Adinda Fitri Sabilla; Usi Lanita; David Kusmawan; Willia Novita Eka Rini; Muhammad Rifqi Azhary (International Journal of Health Engineering and Technology, 2026)
Quality of Work Life (QWL) is an important aspect that influences worker well-being, satisfaction, and productivity. Workers in the tofu industry face various working conditions that potentially affect the quality of work life. This study aims to analyze factors related to the Quality of Work Life of tofu factory workers in Jambi City in 2026. This study used a quantitative design with a cross-sectional approach. The study population was 45 workers and the entire population was sampled using a total sampling technique. The variables studied included salary, work fatigue, length of service, physical workload, mental workload, and work environment. Data analysis was carried out univariately and bivariately using the Chi-Square test with a 95% confidence level. The results showed that most workers had a low Quality of Work Life. Bivariate analysis showed that salary and length of service were significantly related to Quality of Work Life, while work fatigue, physical workload, mental workload, and work environment did not show a significant relationship. It can be concluded that compensation and work experience are factors that play a role in the quality of work life of tofu factory workers. Therefore, efforts are needed to improve workers' welfare by providing better compensation and managing human resources that can improve the quality of work life.